Hot, flat, and crowded : why we need a green revolution, and how it can renew America - Friedman, Thomas L. (New York : Farrar, Straus and Giroux, 2008)
Examines America's loss of focus and national purpose since 9/11, and the global environmental crisis, and shows how the solutions to these two problems are linked.
Includes index.
Keywords: Green movement -- United States; Green technology -- United States; Climatic changes; Power resources -- Environmental aspects; Environmental policy -- United States; Energy policy -- United States; United States -- Environmental conditions; United States -- Social conditions -- 1980-